The Effect of Teaching Materials Based on Local Value Integrated by Character Education through PBL Models on Students' High Order Thinking Skill - Khairil Hadi; Dazrullisa; Hasruddin; Binari Manurung (Britain International for Academic Research (BIAR) Publisher, 2019)
This study aims to know the effect of biology teaching materials based on local wisdom integrated character education through problem-based learning models on students' high order thinking skills. This study uses a quantitative approach and belongs to the type of quasi-experimental research. The research design is the one group’s pre-test-post-test design. The research sample consisted of 111 students from five schools in West Aceh. The data collection used a validation sheet of the lesson plan and high-level thinking test questions. Research data was analysed by statistical average values, normality, homogeneity, and paired sample t test. The research results indicated that the using of biology teaching materials based on local wisdom integrated with character education through problem based learning models has a very significant effect on students' high-level thinking (P=0.00). The instruction that used local wisdom, character education and PBL model have a positive role in the motivating of students, cooperation, discipline, fond of reading, student achievement, and problems solving in accordance with the expected learning outcomes.